How people learn : brain, mind, experience, and school - Bransford, John (Eds.) [et al] (b, 2000)
A resources in which new research about the mind, the brain, and the processes of learning are applied to questions regarding curricula, classrooom settings, and teaching methods
includes index.
Keywords: Learning, Psychology of; Learning -- Social aspects